Navigating India's Climate Finance Maze: Towards a Sustainable Future - Sania Bassi; Diksha (Journal of Advanced Research in Accounting and Finance Management, 2024)
India lies at a critical juncture in its history. A long shadow is cast by climate change, which subsequently jeopardises human health, agriculture, coastal areas, and water supplies. Yet, the country has very ambitious development goals, such as aiming for net-zero emissions by 2070. Significant financial resources, referred to as "climate finance," are essential for navigating this complex route. This article explores the multifaceted realm of climate finance in India, meticulously analysing its sources, issues, and intriguing prospects. We illuminate the different financial avenues that support efforts to combat climate change, ranging from private-sector investments to domestic and public budgets and international collaborations. We also explore the distribution of these resources among multiple sectors. However, obstacles still persist. A scarcity of affordable technologies, capacity-building requirements, and institutional complexity render it difficult to deploy climate funding effectively. When it comes to utilising India's full capabilities in the battle against climate change, these obstacles pose serious challenges. But, in spite of these issues, hope blooms. We examine pioneering developments and creative strategies that present viable paths to overcoming current constraints. This article provides insight into the efficiency of India's various climate finance channels and strategies that will reduce the resource gap and achieve India's grand climate targets, along with suggestions for improving climate funding allocation and application in the areas of accountability, transparency, and inclusivity. In conclusion, this article is focused on shedding insight into India's complex climate financing landscape, enabling stakeholders to effectively deploy resources and advance the country's transition to a thriving and sustainable future.